Fables: A Fun Way to Teach English to Children - Luz Dary Arias Soto (Asociación Colombiana de Profesores de Ingles, 2016)
When dealing with the teaching of English to children, difficulties are likely to arise because sometimes we do not include in the program aspects children love, such as tales, short stories, legends, etc. Furthermore, we can see that those examples from literature are overlooked in the texts we use, specially fables, a narrative genre which is very popular among children ages three to twelve. Though popular, it is neglected in the ESL/EFL curriculum. Hence, I would like to give teachers some suggestions in order to work with literature, and particularly with fables in their classes.